Full suppression of runaway electron generation by the mode penetration of resonant magnetic perturbations during disruptions on J-TEXT. (18th January 2019) - Lin, Z F; Chen, Z Y; Huang, D W; Huang, J; Tong, RH; Wei, Y N; Yan, W; Li, D; Hu, Q M; Huang, Y; Yang, H Y; Li, Y; et al.
Abstract: The avoidance and suppression of runaway electron (RE) generation during disruptions is of great importance for the safe operation of tokamaks. Massive gas injection is used to suppress the generation of REs, but the poor gas mixing efficiency and extremely high density required to suppress RE generation make the full RE suppression unreliable. The magnetic perturbations provide an alternative RE suppression during disruptions. The use of mode penetration induced by resonant magnetic perturbations (RMPs) to suppress RE generation has been investigated on the J-TEXT tokamak. For a sufficiently long mode penetration duration, robust runaway suppression has been reached during the disruptions. The m / n = 2/1 mode RMP with high amplitude excites large magnetic islands inside the plasma and leads to the large-scale destruction of magnetic surfaces during disruptions, which results in RE loss and runaway-free disruptions. The critical island width required for runaway suppression is estimated to be larger than 0.16 as the minor radius. This value might be slightly underestimated because of the misalignment between the electron cyclotron emission diagnostic and the island O-point. NIMROD simulations are used to investigate the effect of magnetic islands on RE generation during disruption, showing that the large magnetic islands have the ability to enhance RE seed loss during disruptions. RMP can excite large magnetic islands in the target plasma without tearing mode and might be a way to prevent RE generation during disruptions.